Immensely Discriminate Routing in Wireless Networks - Sujatha V; E. A. Mary Anitha (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Wireless networks are predictable to grant essential Internet access multimedia traffic service also increasingly such networks have been emerged in real life. However, the application scenarios is indeterminate as well as largely scalable routing is very difficult. Thus require efficient routing schemes in wireless network. In this paper, we propose Immensely Discriminate Routing protocol is used for multihop routing in wireless network. Here, node distance, node link, node trust and node quality of service is evaluated the next hop. This parameters are determined an efficient path in the wireless network.